2011
DOI: 10.3389/fnmol.2011.00012
|View full text |Cite
|
Sign up to set email alerts
|

The roles of glutathione peroxidases during embryo development

Abstract: Embryo development relies on the complex interplay of the basic cellular processes including proliferation, differentiation, and apoptotic cell death. Precise regulation of these events is the basis for the establishment of embryonic structures and the organ development. Beginning with fertilization of the oocyte until delivery the developing embryo encounters changing environmental conditions such as varying levels of oxygen, which can give rise to reactive oxygen species (ROS). These challenges are met by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 185 publications
(210 reference statements)
5
108
1
Order By: Relevance
“…Several recent studies have observed an association between metabolic state and developmental processes, including in hematopoietic, mesenchymal and neural lineages Ufer and Wang, 2011). In the mature intestine, where rapid growth in intestinal crypts feeds differentiated cells onto the villi, it was recently observed that the proliferating progenitor cells exhibit a more glycolytic metabolism than their differentiated counterparts (Stringari et al, 2012;Xiong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have observed an association between metabolic state and developmental processes, including in hematopoietic, mesenchymal and neural lineages Ufer and Wang, 2011). In the mature intestine, where rapid growth in intestinal crypts feeds differentiated cells onto the villi, it was recently observed that the proliferating progenitor cells exhibit a more glycolytic metabolism than their differentiated counterparts (Stringari et al, 2012;Xiong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of this hormone has a negative effect on the processes of cellular growth and tissue differentiation. The connection of a high frequency of embryonic death and fetal abortions with selenium and iodine deficiency was also shown in the works of other authors (26,27).…”
Section: Discussionmentioning
confidence: 77%
“…The ratios and levels of 2GSH/GSSG is the most important cellular redox couple, and a common measure used to assess the cellular redox environment [16]. The state of the redox environment is important for proper development in mammals [12]. In line with this, many genes coding for proteins that maintain the cellular redox system are dynamically regulated during fish embryonic and larval development [21][22][23].…”
Section: Introductionmentioning
confidence: 95%
“…The redox system was focused on due to its importance to overall health. The 100 redox system genes investigated were chosen based on their importance within the redox system and/or because of their membership to gene families that are important within the redox system [12,16,19,[21][22][23]. We found that rotifer-fed larvae had a more reduced cellular environment during development, and had elevated levels of mRNA coding for proteins in glutathione synthesis/recycling, methionine reductase and redox system transcription factor pathways compared to larvae fed copepods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation